2017
DOI: 10.23917/kls.v2i1.5349
|View full text |Cite
|
Sign up to set email alerts
|

English Listening Blended Learning: The Implementation of Blended Learning in Teaching Listening to University Students

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…Various researchers have proved these advantages (e.g. Woltering et al, 2009;Donnelly, 2010;Kırkgöz, 2011;Szymańska & Kaczmarek, 2011;Adas & Bakir, 2013;Aji, 2017). For EFL students, these benefits should be noticed by teachers and school administrators so that they can design BT classes in a way that optimizes student learning and skill development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various researchers have proved these advantages (e.g. Woltering et al, 2009;Donnelly, 2010;Kırkgöz, 2011;Szymańska & Kaczmarek, 2011;Adas & Bakir, 2013;Aji, 2017). For EFL students, these benefits should be noticed by teachers and school administrators so that they can design BT classes in a way that optimizes student learning and skill development.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gilbert and Flores-Zambada (2011), using the blended model, instructors play a roles of a coach, a facilitator, and a cheerleader and their teaching becomes student-centered, which is considered as the most effective approach for language education. Specifically, blended teaching has been proved to be effective for teaching listening (Aji, 2017), speaking (Kırkgöz, 2011), reading (Szymańska & Kaczmarek, 2011), and writing (Adas & Bakir, 2013). BT is an effective method that assists students to acquire more knowledge thanks to the combined benefits of both online and traditional f2f teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Gilbert and Flores-Zambada (2011), using the blended model, instructors play a role of a coach, a facilitator, and a cheerleader and their teaching becomes student-centered, which is considered as the most effective approach for language education. Specifically, BL teaching has been proved to be effective for teaching listening (Aji, 2017), speaking (Kırkgöz, 2011), reading (Szymańska & Kaczmarek, 2011), and writing (Adas & Bakir, 2013). BT is an effective method that assists students to acquire more knowledge thanks to the combined benefits of both online and traditional f2f teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These are given to students and are necessary to join the group. Aji (2017) explored the implementation of blended learning employing Edmodo to teach listening to 28 university students. Data collected through interviews with the listening lecturer, observation of the learning activities, and a questionnaire administered to the students revealed that the blended learning implementation was able to increase the students' listening skills.…”
Section: Learning Effectiveness Using Edmodomentioning
confidence: 99%